2012
DOI: 10.1007/s00247-011-2311-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep sedation during pneumatic reduction of intussusception

Abstract: Deep sedation with propofol did not add any complication to the pneumatic reduction. The fluoroscopic time was short. The success rate of reduction was high,raising the possibility that sedation is beneficial, possibly by smooth muscle relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…In a recent study, Ilivitzki et al . report a success rate of 92% similar to our results. These authors used deep sedation with propofol.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent study, Ilivitzki et al . report a success rate of 92% similar to our results. These authors used deep sedation with propofol.…”
Section: Discussionsupporting
confidence: 92%
“…In a more recent period (2000-2003), a nationwide study performed in the USA reported similar results with a 39% likelihood of radiologic reduction in high-volume pediatric hospitals (2). In a recent study, Ilivitzki et al (12) report a success rate of 92% similar to our results. These authors used deep sedation with propofol.…”
Section: Discussionsupporting
confidence: 88%
“…The primary studies underwent a critical appraisal process and 28 were excluded due to unspecified imaging modality ( n = 10), enema medium ( n = 1), number of attempts at reduction ( n = 6) and number of complications ( n = 11). Consequently, 43 studies were included, 1 SR and 42 studies relating to a single technique …”
Section: Resultsmentioning
confidence: 99%
“…The effect of sedation on outcome is controversial: some studies reported a lower reduction rate [18], while others found a higher rate of success with sedation [31]. A recent paper reports excellent success with propofol, perhaps secondary to long-lasting bowel relaxation [32], while glucagon did not confer any benefit in two independent studies [33,34].…”
Section: Discussionmentioning
confidence: 96%